2018
DOI: 10.1007/s13679-018-0299-6
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Approaches and Weight Loss, Weight Maintenance, and Weight Regain

Abstract: The practice of mindful eating has been applied to the reduction of food cravings, portion control, body mass index, and body weight. Past reviews evaluating the relationship between mindfulness and weight management did not focus on change in mindful eating as the primary outcome or mindful eating as a measured variable. This review demonstrates strong support for inclusion of mindful eating as a component of weight management programs and may provide substantial benefit to the treatment of overweight and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 52 publications
0
56
0
9
Order By: Relevance
“…In terms of weight management, mindful eating encourages a non-judgmental awareness of the physical and emotional sensations of food and supports self-regulation. Over the past few years, there has been increased interest in mindfulness-based interventions (MBI) for weight management and emerging evidence for their inclusion as a component of weight management programs [ 19 21 ].…”
Section: Dietitian’s Perspectivementioning
confidence: 99%
“…In terms of weight management, mindful eating encourages a non-judgmental awareness of the physical and emotional sensations of food and supports self-regulation. Over the past few years, there has been increased interest in mindfulness-based interventions (MBI) for weight management and emerging evidence for their inclusion as a component of weight management programs [ 19 21 ].…”
Section: Dietitian’s Perspectivementioning
confidence: 99%
“…Current proposals suggest that mindfulness may be a way of aiding weight regulation, and preliminary findings are optimistic 15 . In a recent review its found that the practice of mindful eating has been applied to the reduction of food cravings, portion control, body mass index, and body weight 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Dunn C, Haubenreiser M, Johnson M, et al (2018) Curr Obes Rep [5] Purpose of review: There is an urgent need for effective weight management techniques, as more than one third of US adults are overweight or obese. Recommendations for weight loss include a combination of reducing caloric intake, increasing physical activity, and behavior modification.…”
Section: Mindfulness Approaches and Weight Loss Weight Maintenance mentioning
confidence: 99%